2006
DOI: 10.1074/jbc.m511551200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Knockdown of G Protein Subunits Selectively Prevents Receptor-mediated Modulation of Effectors and Reveals Complex Changes in Non-targeted Signaling Proteins

Abstract: Heterotrimeric G protein signaling specificity has been attributed to select combinations of G␣, ␤, and ␥ subunits, their interactions with other signaling proteins, and their localization in the cell. With few exceptions, the G protein subunit combinations that exist in vivo and the significance of these specific combinations are largely unknown. We have begun to approach these problems in HeLa cells by: 1) determining the concentrations of G␣ and G␤ subunits; 2) examining receptor-dependent activities of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 32 publications
10
115
0
1
Order By: Relevance
“…If modified to allow cell penetration (e.g., ref. 50), KB-1753 could effectively block Gα i ·GTP/effector signaling while preserving receptor/heterotrimer coupling and Gβγ-mediated signaling, unlike pertussis toxin which permanently impairs Gα i βγ coupling and signaling via ADP-ribosylation (51) or of siRNA-mediated Gnai transcript silencing which can result in compensatory upregulation of other Gα i/o family members (52). The selective interaction of KB-1753 with Gα i subunits over Gα o (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If modified to allow cell penetration (e.g., ref. 50), KB-1753 could effectively block Gα i ·GTP/effector signaling while preserving receptor/heterotrimer coupling and Gβγ-mediated signaling, unlike pertussis toxin which permanently impairs Gα i βγ coupling and signaling via ADP-ribosylation (51) or of siRNA-mediated Gnai transcript silencing which can result in compensatory upregulation of other Gα i/o family members (52). The selective interaction of KB-1753 with Gα i subunits over Gα o (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of siRNA for Gβ1 and Gβ2 were adapted from Krumins and Gilman (2006). The sequences of siRNAs; siGβ1/Gβ2, 5'-UACGACGACUUCAACUGCATT-3'/5'-UGC-AGUUGAAGUCGUCGUATT-3'; siGFP, 5'-GUUCAGCGU-G U C C G G C G A G T T-3 ' / 5 ' -C U C G C C G G A C A C G C-UGAACTT-3'.…”
Section: Usage Of Sirnamentioning
confidence: 99%
“…For these experiments we confirmed that the Wnt1 signaling pathway is intact and functional as indicated by an increased level of β-catenin upon co-transfection of Wnt1 ( Figure 6A). To further confirm that Gβγ signaling is necessary for the Wnt-mediated loss of Dishevelled, siRNA that can knockdown both Gβ 1 and Gβ 2 (Krumins and Gilman, 2006) was added to HEK293T cells. The cells with that had been given siRNA had lowered Gβ 1 and Gβ 2 , but not other control, mRNAs ( Figure 6B) and had the expected diminished block in the loss of Dishevelled induced by either Wnt1 or Wnt5a ( Figure 6C).…”
Section: Gβγ Signaling Is Necessary For the Wnt-mediated Loss Of Dishmentioning
confidence: 99%
“…These include pools of five~20 nucleotide target-specific siRNAs, pools of three to five lentiviral vector plasmids or particles each encoding target-specific short hairpin RNAs, or non-viral shRNAs specifically targeting Gαq/11 genes. One of the first reported gene knockdown studies of Gα proteins was the knockdown of Gαq and Gα11 gene expression using siRNA in HeLa cells [23]. This work demonstrated an absolute requirement of Gαq/11 to stimulate histamine-mediated PLC activity.…”
Section: Molecular Approaches To the Modulation Of Gαq/11mentioning
confidence: 75%